2015
DOI: 10.1038/nplants.2015.107
|View full text |Cite|
|
Sign up to set email alerts
|

Lineage-specific chromatin signatures reveal a regulator of lipid metabolism in microalgae

Abstract: Alga-derived lipids represent an attractive potential source of biofuels. However, lipid accumulation in algae is a stress response tightly coupled to growth arrest, thereby imposing a major limitation on productivity. To identify transcriptional regulators of lipid accumulation, we performed an integrative chromatin signature and transcriptomic analysis to decipher the regulation of lipid biosynthesis in the alga Chlamydomonas reinhardtii. Genome-wide histone modification profiling revealed remarkable differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 47 publications
4
105
1
Order By: Relevance
“…Some successful approaches have involved the inhibition of lipid catabolism pathways, bypass of carbohydrate synthesis, or modification of transcription factors (Trentacoste et al, 2013;Daboussi et al, 2014;Ngan et al, 2015), while other approaches, such as the overexpression of specific Kennedy pathway components like a DGAT gene, have been less successful in some instances (La Russa et al, 2012). Previous expression of a yeast GPDH in oilseed rape (Vigeolas et al, 2007) and the recent overexpression of a diatom GPDH (Yao et al, 2014) indicate the potential of GPDH manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some successful approaches have involved the inhibition of lipid catabolism pathways, bypass of carbohydrate synthesis, or modification of transcription factors (Trentacoste et al, 2013;Daboussi et al, 2014;Ngan et al, 2015), while other approaches, such as the overexpression of specific Kennedy pathway components like a DGAT gene, have been less successful in some instances (La Russa et al, 2012). Previous expression of a yeast GPDH in oilseed rape (Vigeolas et al, 2007) and the recent overexpression of a diatom GPDH (Yao et al, 2014) indicate the potential of GPDH manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…One recently identified regulatory mutant, tar1, is defective in accumulation of lipid bodies in response to nutrient starvation, and the TAR1 locus was shown to encode a YAK subtype DYRK family protein kinase (Kajikawa et al, 2015). The transcription factors PSR1 and NRR1 have also been postulated as regulators for lipid accumulation during nitrogen starvation (Boyle et al, 2012;Ngan et al, 2015), and the transcription factor CHT7 is required for TAG remobilization when starved cells are returned to nutrient-replete media (Tsai et al, 2014). To date, no putative regulatory mutants have been identified that uncouple TAG accumulation from nitrogen starvation or acetate supplementation as we observed in vip1-1, nor have regulatory mutants been described that cause increased TAG and lipid overaccumulation compared with wild-type cells.…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…PSR1 regulates some of the essential genes that are associated with lipid and starch biosynthesis (Bajhaiya et al, 2016). TAG accumulation is increased without affecting cell growth in the PSR1-overexpressing strain CC-125 (Ngan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…TAG accumulation is a complicated process in C. reinhardtii, and therefore additional TFs might be involved. The use of a low PiÀresponsive promoter and a TF such as PSR1 for TAG overproduction has shed some light on the clarification of regulatory mechanisms involved in TAG synthesis under P-starvation in C. reinhardtii (Ngan et al, 2015;Bajhaiya et al, 2016). Concomitantly with TAG accumulation, membrane remodeling is a typical response under P-starvation and occurs widely throughout oxygenic photosynthetic organisms from cyanobacteria and phytoplankton to land plants (Nakamura et al, 2009;Hori et al, 2016;Shemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%